2015
DOI: 10.1177/0267659115580666
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of cardiopulmonary bypass circuit with new polymer Senko E-Ternal CoatingTM

Abstract: The SEC-coated circuit demonstrated equivalent biocompatibility to the PMEA-coated circuit. SEC-coated circuits are, therefore, favorably comparable to PMEA-coated circuits for clinical use in CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The three polymers comprising SEC are (1) a long-chain alkyl group that enhances the affinity between the coating and the base materials and improves durability; (2) a water-repellent silicone polymer based on dimethylpolysiloxane that regulates complement activation; and (3) a highly hydrophilic polyethylene glycol chain that regulates the activation and cascade reaction of the coagulation system by suppressing the adhesion or adsorption of platelets and plasma proteins. Fukui et al 2 compared the biocompatibility of SEC-coated and poly-2-methoxyethyl acrylate (PMEA)-coated circuits, the latter being a material used commonly for CPB circuits. They demonstrated that the SEC-coated circuit has biocompatibility equivalent to that of the PMEA-coated circuit, with no significant differences in coagulation or inflamma-tion during CPB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The three polymers comprising SEC are (1) a long-chain alkyl group that enhances the affinity between the coating and the base materials and improves durability; (2) a water-repellent silicone polymer based on dimethylpolysiloxane that regulates complement activation; and (3) a highly hydrophilic polyethylene glycol chain that regulates the activation and cascade reaction of the coagulation system by suppressing the adhesion or adsorption of platelets and plasma proteins. Fukui et al 2 compared the biocompatibility of SEC-coated and poly-2-methoxyethyl acrylate (PMEA)-coated circuits, the latter being a material used commonly for CPB circuits. They demonstrated that the SEC-coated circuit has biocompatibility equivalent to that of the PMEA-coated circuit, with no significant differences in coagulation or inflamma-tion during CPB.…”
Section: Discussionmentioning
confidence: 99%
“…However, drawbacks include heparin-related bleeding, heparin-induced thrombocytopenia, and contamination of heparin from the porcine intestine from which it is usually extracted. 2,3 SEC-1 coat™ (SEC; TOYOBO Co., Ltd, Osaka, Japan) is a commercially available coating material designed to improve the biocompatibility of CPB circuit surfaces in contact with blood. Fukui et al 2 demonstrated in adults that SEC-coated CPB circuits have excellent biocompatibility with regard to minimizing coagulation and inflammation during aortic valve replacement surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparin, trillium, poly-2-methoxyehylacrylate, phosphorylcholine, and senko e-ternal coating has been used till date. [ 63 64 65 66 67 68 69 70 ] The purpose of modifying the surface of extracorporeal circuit is to prevent the inflammatory response that occurs during CPB. Therefore, the majority of studies done on surface modified circuits have evaluated the rise and fall in the serum levels of inflammatory cytokines and molecules.…”
Section: Surface Modified Bypass Circuitsmentioning
confidence: 99%
“…This biocompatible polymer coating agent (BPA) is composed of a hydrophobic backbone adherent to the surface, and a hydrophilic blood-contacting layer. The hydrophilic layer swells when blood contacts it, creating a water-filled layer that maintains protein conformation and prevents surface activation ( 10 ), and many studies have reported a reduction in the circuit's thrombogenecity, or reduction in the heparin dose needed to achieve adequate anticoagulation by BPA coating ( 11 15 ). In our previous study, a hemoconcentrator, which has similar function as the hemodialyzer in cardiopulmonary bypass circuit, was probatively coated with BPA and investigated as regards hydrokinetics.…”
Section: Introductionmentioning
confidence: 99%